Pretreatment of wastewater sludge by pulsed electric field application at different pH conditions - Hacıosmanoğlu, Gülenay. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2010., 2010)
Keywords: Waste water sludge; Sludge disintegration; Pulsed electric field; Sludge dewatering; Aerobic digestion|Wastewater treatment processes produce large amounts of sludge to be stabilized and dewatered before safe utilization or disposal. Biological degradation processes are usually preferred sludge stabilization methods since they are cost-effective and environmentally friendly. However they have some limitations in terms of long treatment times and large working areas requirements. To overcome these limitations and to improve sludge biodegradability, different pretreatment methods are developed. The objective of this study is to evaluate pulsed electrical field (PEF) application as a sludge pretreatment method. For this purpose, PEF up to 30 kV/cm with different pH conditions was applied on sludge. The results demonstrated that PEF pretreatment deteriorated sludge dewaterability measured in terms of specific resistance to filtration and capillary suction time. However PEF pretreatment improved sludge compactibility measured in terms of cake dry solids content. According to semi-continuous aerobic biodegradability tests, the mean COD removal was increased by 7.8 % and the mean VS removal was increased by 4.6 %, for the reactors fed with PEF pretreated sludge compared to the control reactors. Batch aerobic biodegradation experiments demonstrated that the mean improvements supplied by PEF pretreatment were 3.4 and 2.2 %, for COD and VS removals, respectively.
Keywords: Sewage sludge.; Sewage -- Purification -- Biological treatment.